Manajemen Komunikasi Army Help Center (AHC) Indonesia Dalam Menangani Kasus Mental Illness Penggemar Bangtan Sonyeondan (BTS - Riyantie, Mayang; Romli, Romli; Shebira, Hani; Barizki, Rezzi Nanda (LUGAS Jurnal Komunikasi, 2022)
Communication Management is a way of communication carried out by an organization in order to achieve certain goals. This communication management is implemented by the Army Help Center (AHC) in dealing with cases of mental illness in BTS fans. Korean Boyband fans are always characterized as bigotry or excessive behavior, so that they often make their fans feel inferior or experience other mental disorders. The purpose of this study was to determine the AHC communication management in dealing with cases of mental illness of BTS fans. The research method used is descriptive qualitative research method with data collection techniques through interviews and observation as well as literature study techniques and also documentation.The results of the study show that communication management carried out by AHC is by providing social media Twitter as a media for consultation with ARMY, then seeking and or receiving data from fans who consult on their problems (Fact Finding), Planning steps for communication and problem solving approaches using the right language and easy to accept (Planning), Communicating through social media and providing good emotional control and a humanist approach with positive communication language (Action and Communications) and conducting evaluations by controlling the fans' condition after consultation with AHC (Evaluating). From the findings, AHC provides communication therapy as comfortable as possible to BTS fans so that the mental illness they experience can be resolved properly. Communication barriers found in this study are semantic barriers in the form of difficulty interpreting messages and technical barriers in the form of difficulty finding free time.